2012
DOI: 10.1007/s11418-012-0696-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenylalanine on Taxol production and antioxidant activity of extracts of suspension-cultured hazel (Corylus avellana L.) cells

Abstract: Taxol is produced by a few microorganisms and plants such as yew (Taxus sp.). Recent researches have shown that hazel (Corylus avellana L.) is also able to produce Taxol. In the present study, effects of different concentrations of phenylalanine (Phe) on the production of Taxol, antioxidant activity, and cytotoxic effects of extracts of suspension-cultured hazel cells were investigated. The cells were treated with different concentrations of Phe on day 7 of subculture and were harvested on day 14. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…Our findings (Table 3) are in line with the results reported earlier by Arafa et al (2015) and Arafa and Aly (2018), who detected that the highest scavenging activity values in calli of stem, root, and petiole explants of Daucua carota L. carota was recorded with using phenylalanine as amino acid precursor and Bemani et al (2012) who increased more amounts of Taxol and antioxidant activity by increment of phenylalanine supply in the extract of suspension-cultured hazel (Corylus avellana L.) cells. Furthermore, our investigations are in partial harmony with those of Ghasemzadeh et al (2012) who reported that SA improved the production of some chemical structures such as fisetin and anthocyanin who possess more potency as antioxidant activity than the control in ginger varieties and Hadian-Deljou et al (2017) who attained more total phenolics and antioxidant activity by salicylic acid application using 2 mM concentration at the earlier stages of cold storage and using 1 mM concentration at the end of cold storage for red delicious apples.…”
Section: Evaluation the Percentage Of Free Radical Scavenging Capacitsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings (Table 3) are in line with the results reported earlier by Arafa et al (2015) and Arafa and Aly (2018), who detected that the highest scavenging activity values in calli of stem, root, and petiole explants of Daucua carota L. carota was recorded with using phenylalanine as amino acid precursor and Bemani et al (2012) who increased more amounts of Taxol and antioxidant activity by increment of phenylalanine supply in the extract of suspension-cultured hazel (Corylus avellana L.) cells. Furthermore, our investigations are in partial harmony with those of Ghasemzadeh et al (2012) who reported that SA improved the production of some chemical structures such as fisetin and anthocyanin who possess more potency as antioxidant activity than the control in ginger varieties and Hadian-Deljou et al (2017) who attained more total phenolics and antioxidant activity by salicylic acid application using 2 mM concentration at the earlier stages of cold storage and using 1 mM concentration at the end of cold storage for red delicious apples.…”
Section: Evaluation the Percentage Of Free Radical Scavenging Capacitsupporting
confidence: 92%
“…Data exhibited in Figs. 3, 4, and 5 reported that (El-Nabarawy et al, 2015) who revealed that higher concentrations of phenylalanine inhibited the fresh weight of Zingiber officinale calli in comparison with the fewer levels, Bemani et al (2012) who found that up to 3 mM of PA affected adversely hazel cells growth of Corylus avellana L. and at 6 mM of PA had no significant influence on cells dry weight and Bosila et al (2012) who confirmed the significant differences for calli dry weight according to the amino acid or precursor levels, where expanding the concentrations of PA (100 and 200 mg/l) decreased calli dry weight of Silybum marianum L. In this study, it was found that SA had positive capacity and good response rather than PA for high performance of gardenia calli growth. This achievement is in line with various earlier studies such as Lingakumar et al (2014) who initiated calli of Vigna mungo on MS medium containing 0.5 ppm SA then induced high percentage of callus induction frequency using 1 ppm SA, Quiroz-Figueroa and Mendez-Zeel (2001) who reported that SA is a hormone like chemical which enhance in vitro regeneration for plenty of plant species including Coffea arabica, and (Hao et al, 2006) who increased calli dry weight of naked oat using SA.…”
Section: Effect Of Phenyl Alanine or Salicylic Acid On Calli Growth Cmentioning
confidence: 99%
“…Phenylalanine (Phe) has shown positive effect on Taxol production by suspension-cultured hazel cells and its cytotoxic effects. It is interesting its cytotoxic activity was more standard Taxol [22]. Cell culture of hazel is eaiser and faster than yew and in future it can be a more relibele approach for Taxol production.…”
Section: Alternative Speciesmentioning
confidence: 99%
“…Published documents reveal that phenylalanine (Phe), an aromatic amino acid, is the substrate of phenylalanine ammonia-lyase and catalyzes the reductive deamination of L-phe into trans-cinnamic acid as the first step of the biosynthesis of plant phenolic compound. [ 11 ] Bemani et al ., in 2012,[ 12 ] found that Phe up to 3 mM had no significant effect on the growth of hazel cells and at 6 mM, it affected the dry weight adversely. In the search for alternatives for production of desirable medicinal compounds from plants, biotechnological approaches, especially plant tissue cultures, are found to have potential as a supplement to traditional agriculture in the industrial production of bioactive plant metabolites.…”
Section: Introductionmentioning
confidence: 99%